Natural Competence Is a Major Mechanism for Horizontal DNA Transfer in the Oral Pathogen Porphyromonas gingivalis - Gena D. Tribble (American Society for Microbiology, 2012)
ABSTRACT Porphyromonas gingivalis is a Gram-negative anaerobe that resides exclusively in the human oral cavity. Long-term colonization by P. gingivalis requires the bacteria to evade host immune responses while adapting to the changing host physiology and alterations in the composition of the oral microflora. The genetic diversity of P. gingivalis appears to reflect the variability of its habitat; however, little is known about the molecular mechanisms generating this diversity. Previously, our research group established that chromosomal DNA transfer occurs between P. gingivalis strains. In this study, we examine the role of putative DNA transfer genes in conjugation and transformation and demonstrate that natural competence mediated by comF is the dominant form of chromosomal DNA transfer, with transfer by a conjugation-like mechanism playing a minor role. Our results reveal that natural competence mechanisms are present in multiple strains of P. gingivalis, and DNA uptake is not sensitive to DNA source or modification status. Furthermore, extracellular DNA was observed for the first time in P. gingivalis biofilms and is predicted to be the major DNA source for horizontal transfer and allelic exchange between strains. We propose that exchange of DNA in plaque biofilms by a transformation-like process is of major ecological importance in the survival and persistence of P. gingivalis in the challenging oral environment. IMPORTANCE P. gingivalis colonizes the oral cavities of humans worldwide. The long-term persistence of these bacteria can lead to the development of chronic periodontitis and host morbidity associated with tooth loss. P. gingivalis is a genetically diverse species, and this variability is believed to contribute to its successful colonization and survival in diverse human hosts, as well as evasion of host immune defenses and immunization strategies. We establish here that natural competence is the major driving force behind P. gingivalis DNA exchange and that conjugative DNA transfer plays a minor role. Furthermore, we reveal for the first time the presence of extracellular DNA in P. gingivalis biofilms, which is most likely the source of DNA exchanged between strains within dental plaque. These studies expand our understanding of the mechanisms used by this important member of the human oral flora to transition its relationship with the host from a commensal to a pathogenic relationship.